Zagraniczne inwestycje bezpośrednie jako kanał transferu technologii w rozwiniętych krajach kapitalistycznych - Czerwieniec, Eugeniusz (Digitalizacja i deponowanie archiwalnych zeszytów RPEiS sfinansowane przez MNiSW w ramach realizacji umowy nr 541/P-DUN/2016, 1990)
Direct capital investment made abroad by big multinational corporations are in principle the main channel of the international transfer of modern technology. One may even say that the growth of big multinational firms and development of modern technology are mutually interdependent. The almost simultaneous appearance of these two phenomena countributed to the turn in the way of thinking in classical theories of international trade. Since that time it has been suggested that theoretical considerations should include new factors of production and that hitherto existing views on their international mobility may be regarded as absolete. A long-term exploitation of technological primacy of a multinational corporation on foreign markets is realized due to the transfer of new technologies through the following channels: export of production goods, sale of licences, foreign direct investment and the migration of scientists and qualified technical personnel. The determination of relative significance of particular channels is a difficult task. It seems that the most important means of transfer of modern technology is foreign direct investment. The importance of other channels is to a great extent conditioned upon the character and technology of production, and the country and period of transfer. Nowadays, it is generally believed that the spread and efficient exploitation of new technology is an important source of economic growth of developed industrial countries, brings about the changes in the structure of international trade, contributes to the development of national technological skills and brings so-called scientific advantages as well as advantages in the sphere of management and organization.
Foreign direct investment as a channel of the transfer of technology in development capitalistic countries